Clinical profile of thrombocytopenia in tropical infectious diseases - Kothari, Jaini S.; Shah, Archana N.; Prajapati, Rajal B. (International Journal of Contemporary Pediatrics, 2020)
Background: In an infant or child thrombocytopenia can occur due to large spectrum of illness ranging from tropical infection to malignancy or bone marrow failure. Management is decided by the severity of thrombocytopenia, associated risk factors and underlying illness. Children with thrombocytopenia may be asymptomatic – detected by complete blood count for some other clinical issue or symptomatic-presenting with mucosal and/or cutaneous bleeding and rarely central nervous system bleed. Aim of this research is to study the distribution of patients with thrombocytopenia, their grading according to platelet counts and etiology with special focus to infective causes, other complications in these infections and recovery from thrombocytopenia. Methods: This is an observational analytical retrospective study. 100 randomly selected pediatric patients (6 months to 12 years) admitted in pediatric ward with documented thrombocytopenia (platelet count <150,000/ul) on admission or at any point of time during hospitalisation are enrolled and analyzed. Results: 91% patients have thrombocytopenia associated with infective causes, of which 44% have dengue. 7 patients in study have bleeding manifestations and 3 required platelet transfusion. 50% patients with dengue with thrombocytopenia have leucopenia and 2% have pancytopenia. 57.1% patients with enteric fever with thrombocytopenia show elevated alanine aminotransferase (ALT) levels. Mean platelet recovery time is 2 to 4 days for various infections. Conclusions: Majority of patients do not have bleeding manifestations, and they are mainly seen with severe thrombocytopenia associated with infections. Requirement of platelet transfusion is not common and is seen only in patients with severe thrombocytopenia with significant bleeding manifestation.